Relationship between ultrasonographic nerve morphology and severity of diabetic sensorimotor polyneuropathy - Arumugam, T.; Razali, S.N.O.; Vethakkan, S.R.; Rozalli, F.I.; Shahrizaila, N. (Blackwell Publishing, 2016)
Background and purpose: In the current study, the aim was to characterize the nerve ultrasound cross-sectional areas (CSAs) of type 2 diabetic patients with diabetic sensorimotor polyneuropathy (DSP) of different severities. Methods: A hundred symptomatic DSP patients and 40 age-matched healthy controls were prospectively recruited. DSP severity was ascertained through the Toronto Clinical Scoring System (TCCS). Nerve electrophysiology and ultrasound were performed on both lower limbs and the non-dominant upper limb. Results: The sural nerve was inexcitable in 19.1% of mild, 40.0% of moderate and 69.0% of severe DSP groups. In contrast, CSAs were measurable in all nerves of DSP patients and were significantly larger compared to controls. Patients with severe DSP had significantly larger ulnar, peroneal, tibial and sural nerves compared to mild DSP patients. By receiver operating characteristic curve analysis, the cut-off value for the sural nerve at 2 mm2 was a good discriminator (area under the curve 0.88) between the presence and absence of DSP (sensitivity 0.90; specificity 0.74) but performed less well in discriminating between the severity of DSP (cut-off 2.75 mm2; area under the curve 0.62; sensitivity 0.59; specificity 0.73). Significant correlations were demonstrated between TCSS scores, most neurophysiology parameters and CSAs of the ulnar, peroneal, tibial and sural nerves. Conclusion: Nerve ultrasound in DSP reveals enlarged CSAs and these changes worsen with increasing disease severity, thus serving as a useful diagnostic tool especially when neurophysiology is unrevealing.